Exploring English Speaking Problems in Higher Education: Pre-Service English Teachers’ Perspectives - Wahyuningsih, Sri; Maisyanah, Maisyanah (Journal of English Teaching and Learning Issues, 2021)
The purpose of this present study was to explore a dozen of English-speaking problems encountered by pre-service English teachers in one of Indonesian Higher Educations. The data of this qualitative study were garnered through semi-structured interviews to ten pre-service English teachers at Institut Agama Islam Negeri Kudus and relevant documentations. The results revealed that speaking English fluently is not really easy for the pre-service English teachers. In addition, they encountered some problems including lack of appropriate vocabulary, grammar mastery, correct pronunciation, and lack of confidence. This study presents an implication in accordance with the curriculum development of speaking course in higher education particularly at Institut Agama Islam Negeri Kudus including the need of reformulating the speaking course curriculum which emphasizes on the integration of technology to arouse the spirits among pre-service English teachers in speaking English. Moreover, the need of providing more chance to speak English for them both inside and outside of the class.